Enantioselective synthesis of (S,S)-ethambutol using proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination - Kotkar, Shriram P.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2006)
An efficient enantioselective synthesis of (S,S)-ethambutol, a tuberculostatic antibiotic, has been achieved in 99% ee via both proline-catalyzed alpha-aminooxylation and alpha-amination of n-butyraldehyde as the key step. (c) 2006 Elsevier Ltd. All rights reserved.